1998
DOI: 10.1016/s0042-6989(97)88333-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatial frequency discrimination: Visual long-term memory or criterion setting?

Abstract: A long-term sensory memory is believed to account for spatial frequency discrimination when reference and test stimuli are separated by long intervals. We test an alternative proposal: that discrimination is determined by the range of test stimuli, through their entrainment of criterion-setting processes. Experiments 1 and 2 show that the 50% point of the psychometric function is largely determined by the midpoint of the stimulus range, not by the reference stimulus. Experiment 3 shows that discrimination of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
81
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 30 publications
5
81
1
Order By: Relevance
“…This has been called "sensory memory theory" (Lages & Treisman, 1998). In contrast, the phenomenon of "change blindness" (Rensink, O'Regan & Clark, 1997) might be defined as the inability to discriminate between stimuli which are separated by a time interval.…”
Section: Introductionmentioning
confidence: 99%
“…This has been called "sensory memory theory" (Lages & Treisman, 1998). In contrast, the phenomenon of "change blindness" (Rensink, O'Regan & Clark, 1997) might be defined as the inability to discriminate between stimuli which are separated by a time interval.…”
Section: Introductionmentioning
confidence: 99%
“…Lages and Treisman (1998), however, showed that spatial frequency discrimination data that had been thought to demonstrate visual long-term memory could be accounted for by criterion setting at the decision stage. Individual performance in a given trial was based on a comparison between the test stimulus and a decision criterion, rather than on a sensory memory of the reference stimulus.…”
mentioning
confidence: 97%
“…Individual performance in a given trial was based on a comparison between the test stimulus and a decision criterion, rather than on a sensory memory of the reference stimulus. For example, spatial frequency discrimination was not impaired when observers had to guess a midpoint from a few test stimuli in the absence of a reference (Lages, 1998; Experiment 2 in Lages & Treisman, 1998).…”
mentioning
confidence: 99%
“…In other words, according to IRM, the negative Type B effect can either be present or absent, however, it cannot reverse. This general mechanism 1 Please note that even such an extended version could not account without further assumptions for sequential effects reported in the literature Dyjas et al 2012;Lages and Treisman 1998). Nevertheless, such sequential effects are consistent with the basic mechanism of the Internal Reference Model outlined in the following paragraphs.…”
mentioning
confidence: 55%